Model Reproduksi Ikan Berdasarkan Korelasi Panjang, Berat, dan Kematangan Gonad - Bahri, Anjas Sasana; Arifin, Sunanto (Idarotuna : Journal of Administrative Science, 2024)
his study aims to analyze the relationship between length-weight, condition factor (K), gonadal maturity stages (GMS), and reproductive strategies of nine fish species captured in the Brantas River, Puri District, Mojokerto. The results indicate that most fish were in GMS II (developing), suggesting that the spawning season was ongoing. Four species—Betok, Kothok, Gatol, and Wader Pari—were found in GMS IV/V, marking the peak or end of the spawning period. The reproductive strategies of these fish species were classified into three main models: seasonal synchronous spawning, batch spawning, and pre-reproductive growth strategies. The findings highlight that the fish community in this river demonstrates flexible reproductive patterns, which serve as an adaptation to the fluctuating environment of the tropical river ecosystem. The contribution of this study lies in the development of a comprehensive model that links key biological parameters—length, weight, condition factor, and gonadal maturity—to the reproductive strategies of riverine fish. This model provides valuable insights into how fish species adapt their reproductive behaviors to the dynamic environmental conditions of tropical river ecosystems. The findings offer practical applications for sustainable fishery management and conservation, enabling more effective monitoring and conservation strategies tailored to specific ecological conditions.